Highly active new alpha-diimine nickel catalyst for the polymerization of alpha-olefins - Liu, Hua-Rong; Gomes, P. T.; Costa, S. I.; Duarte, M. T.; Branquinho, R.; Fernandes, A. C.; Chien, J. C. W.; Singh, R. P.; Marques, Maria M. (Journal of Organometallic Chemistry, 2005)
A new silylated alpha-diimine ligand, bis[N,N `-(4-tert-butyl-diphenylsilyl-2,6-diisopropylphenyl)imino]acenaphthene 3, and its corresponding Ni(II) complex, {bis[N,N `-(4-tert-butyl-diphenylsilyl-2,6-diisopropylphenyl)imino]acenaphthene} dibromonickel 4, have been synthesized and characterized. The crystal structures of 3 and 4 were determined by X-ray crystallography. In the solid state, complex 4 is a dimer with two bridging Br ligands linking the two nickel centers, which have square pyramidal geometries. Complex 4, activated either by diethylaluminum chloride (DEAC) or methylaluminoxane (MAO) produces very active catalyst systems for the polymerization of ethylene and moderately active for the polymerization of propylene. The activity values are in the order of magnitude of 10(7) g PE (mol Ni [E] h)(-1) for the polymerization of ethylene and of 10(5) g PP (mol Ni [P] h)(-1) for the polymerization of propylene. NMR analysis shows that branched polyethylenes (PE) are obtained at room or higher temperatures and almost linear PE is obtained at 0 degrees C with 4/DEAC. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: alpha-diimine nickel complex; Ethylene polymerization; late transition-metal; propylene polymerization